PENGARUH KETERLIBATAN KARYAWAN TERHADAP KEPUASAN KERJA DENGAN PENGHARGAAN (REWARD) SEBAGAI PEMEDIASI PADA BANK SYARIAH DI KOTA BANDA ACEH - Risa Maulinda, Nurlina (Departemen Manajemen, 2018)
Abstract: This study aims to determine the effect of employee involvement to job satisfaction with reward as a mediating. The empirical study conducted at Sharia Bank in Banda Aceh City used a questionnaire as a research instrument, which samples in this study of 120 people. Probability sampling is used as a sampling technique with Total Sampling. Methods HLM (Hierarchical Linear Modelling) is used as a method of data analysis using software IBM SPSS 22. These results indicate that the employee involvement positive and significant impact on job satisfaction, employee involvement significantly and positively related to reward, reward have a positive and significant effect on job satisfaction and in addition showed that the reward mediate effect on employee involvement to job satisfaction as partial mediation.